Analysis and Application of Critical Pressure Prediction Model for Surface Leakage of Underwater Shallow Buried Jacking-Pipe Grouting - Ziguang Zhang; Yong He; Xiaopeng Li; Xiang Li; Lin Wei; Feifei Chen (Buildings)
Jacking-pipe construction has the advantages of high mechanization, low environmental impact and fast construction speed. It is widely used in the project of underground pipeline under river. However, jacking-pipe grouting under shallow burial conditions is prone to cause surface bubbling problems. Based on the jacking-pipe project of Meichong Lake in Changfeng County, Hefei, this paper discussed the mechanism of grouting surface leakage, and defined the relationship between the critical pressure of jacking-pipe grouting and the ultimate pressure of shear damage of mud jacket. Mechanical model of surface leakage from shallow buried jacking-pipe grouting was established. A general mathematical expression for the grouting critical pressure was derived and a sensitivity analysis was performed. A numerical model was established based on the background engineering, and multiple sets of grouting pressure conditions for simulation and analysis were set up. The results showed that the cohesive force <semantics>c</semantics>, the angle of internal friction <semantics>φ</semantics>, and the overburden thickness <semantics>hs</semantics> were all approximately linearly and positively correlated with the critical pressure of grouting. When the grouting pressure was less than 197.54 kPa the surface settlement increased. When this value was exceeded the surface displacement changed from settlement to uplift and the risk of slurry bubbling increased significantly. The theoretical calculation matched the value of grouting critical pressure from numerical simulation. The actual grouting pressure in the project was lower than the theoretical grouting critical pressure value and no slurry bubbling occurred during construction, which had verified the reliability of the theoretical model. This study can provide theoretical basis and investigation ideas for the setting of reasonable grouting pressure in similar projects.